Formulation and evaluation of dispersible taste masked tablet of roxithromycin - Mundada, A S; Meshram, D R; Banbale, H B; Bhalekar, M R; Avari, J G (Asian Journal of Pharmaceutics (AJP), 2014)
Roxithromycin is a broad spectrum, semisynthetic macrolide antibiotic, having bitter taste. In the present study, an attempt has been made to mask the bitter taste of roxithromycin by complexation technique. Weak cation exchange resins Indion 214 and Amberlite IRP64, polymer carbopol 934P were used in formulation of complexes with the drug. The loading process was optimized for the pH of loading solution and resin or polymer:drug ratio.The complexes were evaluated for bulk density, angle of repose, taste masking, and in vitro drug release. In vitro drug release studies showed more than 80% drug release from the optimized formulation within 30 min. Amberlite IRP64 was found to be better complexing agent for masking the bitter taste of roxithromycin.